Composite for secondary battery electrode
The composite of fibrous carbon uniformly dispersed on active materials in secondary battery electrodes addresses aggregation issues, enhancing conductivity and battery performance by reducing resistance, resulting in high-output and long-life batteries.
Patent Information
- Application Number
- JP2023108257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Existing methods for producing secondary battery electrodes using carbon nanotubes as conductive agents face issues with aggregation, requiring large amounts to form a conductive network, leading to uneven distribution and increased electrode resistance.
A composite for secondary battery electrodes is developed, comprising fibrous carbon with controlled dispersion and adsorption on active materials, ensuring a uniform distribution and low volume resistivity, achieved by specific thermogravimetric-differential thermal analysis and volume resistivity criteria.
The composite achieves high conductivity, improving battery performance with reduced electrode resistance, leading to high-output and long-life nonaqueous electrolyte secondary batteries.
Smart Images

Figure 2025007086000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite for a secondary battery electrode, and an electrode, a secondary battery, and a device each using the composite. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.
[0003] The electrodes of secondary batteries are prepared by coating a composite slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, etc., on a current collector. A conductive material dispersion liquid in which a conductive material is dispersed in a dispersion medium is prepared, and an active material and a binder resin are added to the conductive material dispersion liquid to prepare a composite slurry, so that the conductive material is uniformly dispersed and contained in the electrode film, and the conductivity of the electrode film can be improved. In order to increase the capacity of secondary batteries, an increase in the ratio of active materials in the electrodes is desired, and carbon nanotubes, which can efficiently form a conductive network even with a small amount as a conductive agent and reduce electrode resistance, are considered promising. On the other hand, in order to achieve low resistance with the addition of a smaller amount of carbon nanotubes, it is effective to use carbon nanotubes with a small average outer diameter and large fiber length. However, these carbon nanotubes have strong cohesive forces, making it difficult to distribute them uniformly in the electrode. In order to efficiently form a conductive network in the electrode and ensure a conductive path to the active material, a method has been proposed in which a composite is used in which a conductive material such as carbon nanotubes is adsorbed onto the surface of the active material in advance.
[0004] Patent Document 1 discloses an example in which a negative electrode active material and graphite are combined by mechanochemical treatment to produce a negative electrode active material having high electronic conductivity and high mechanical strength. Patent Document 2 discloses an example of producing a negative electrode material for lithium ion secondary batteries that exhibits good charge / discharge characteristics and cycle characteristics, particularly excellent rapid charge / discharge efficiency, by combining a negative electrode active material and fibrous carbon through mechanochemical treatment. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent application 2019-502824 [Patent Document 2] Patent Publication No. 2006-008462 Summary of the Invention [Problem to be solved by the invention]
[0006] In the method disclosed in Patent Document 1, graphite is used as a conductive additive, but since no dispersant is included, the graphite is prone to agglomeration, and there is a problem in that a large amount of conductive additive is required to form a conductive network. The method disclosed in Patent Document 2 has the problem that since a dispersant is not used, the carbon nanotubes are prone to aggregation, and a large amount of carbon nanotubes is required to form a conductive network.
[0007] In order to solve the above problems, the present invention aims to provide a composite for a secondary battery electrode, in which carbon nanotubes are uniformly dispersed and adsorbed by a composite method using an active material and fibrous carbon, thereby achieving high electrical conductivity. [Means for solving the problem]
[0008] A composite for a secondary battery electrode comprising fibrous carbon and a negative electrode active material, characterized in that the fibrous carbon has an exothermic peak temperature of 530°C or less as measured by simultaneous thermogravimetry and differential thermal analysis in an oxygen atmosphere, and has a volume resistivity of 1000 Ω cm or less under a load of 20 kN.
[0009] 2. The composite for a secondary battery electrode according to claim 1, wherein the content of the fibrous carbon is 20 mass % or less based on the mass of the composite for a secondary battery electrode.
[0010] The present invention relates to an electrode for a secondary battery, comprising the above-mentioned composite for a secondary battery electrode.
[0011] The present invention relates to a secondary battery including the above-mentioned secondary battery electrode.
[0012] The present invention relates to a vehicle or device equipped with the secondary battery. Effect of the Invention
[0013] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 shows an example of a TG curve and a DTA curve in TG-DTA, and a combustion temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.
[0016] In this specification, carbon nanotubes may be referred to as "CNTs." In addition, in this specification, a carbon nanotube dispersion may be simply referred to as a "CNT dispersion" or a "dispersion." In addition, a composite for secondary battery electrodes may be referred to as an "electrode composite" or a "composite."
[0017] <Composite for secondary battery electrodes> The electrode composite for a secondary battery contains an active material and fibrous carbon, and may further contain, optionally, a dispersant and a binder resin. The electrode composite may further contain optional components.
[0018] When the electrode composite of the present invention has a combustion temperature of the fibrous carbon in an oxygen-containing atmosphere of 530°C or less and a volume resistivity of 1000 Ω·cm or less under a load of 20 kN, the fibrous carbon on the active material becomes loose and uniformly adsorbed in the composite, and an electrode for a secondary battery having good electrode resistance can be obtained.
[0019] The temperature of the exothermic peak of the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the maximum exothermic peak top (A in FIG. 1) derived from the combustion of fibrous carbon is read and determined as the temperature of the exothermic peak of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Note that, in the case of graphite or the like, whose combustion temperature is close to that of fibrous carbon and the exothermic peaks partially overlap, the exothermic peak top can be determined by peak separation of the components derived from the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even with the same type of fibrous carbon, the decomposition temperature changes depending on the state of aggregation, and the combustion decomposition temperature is higher for strong aggregation.
[0020] When the combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is 530°C or lower, the fibrous carbon on the active material is adsorbed in a loose state. It is more preferable that the combustion temperature is 500°C or lower. When the combustion temperature is 530°C or higher, the fibrous carbon is adsorbed in an aggregated state on the active material, so that the contact area between the active material and the fibrous carbon is small. In that case, when the composite is used as a secondary battery electrode, the electron conduction path from the fibrous carbon to the active material is reduced, leading to deterioration of the battery characteristics.
[0021] When the volume resistivity of the electrode composite for secondary batteries is 1000 Ω·cm or less, uneven distribution of the fibrous carbon in the composite does not occur, and the electrode resistance can be reduced when the composite is used as a secondary battery electrode. A volume resistivity of 100 Ω·cm or less is preferable, and a volume resistivity of 10 Ω·cm or less is even more preferable.
[0022] The volume resistivity of the electrode composite for secondary batteries can be determined by performing resistivity measurement based on the four-terminal four-probe method. Specifically, four needle-like probes (electrodes) are brought into contact with the secondary battery electrode composite to be measured, and the resistance of the test piece is calculated from the current passed between the two outer probes and the potential difference generated between the two inner probes. The volume resistivity of the CNTs can then be calculated from the measured resistance and the thickness of the test piece. The measurement is performed using a volume resistivity measuring device (for example, the low-resistance version of the automatic powder resistivity measuring system MCP-PD600 manufactured by Nitto Seiko Analytech Co., Ltd.).
[0023] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.
[0024] As mentioned above, when the combustion temperature is 530°C or less, it indicates that the fibrous carbon in the composite is in a crushed state, and when the volume resistivity is 1000 Ω·cm or less, it indicates that the fibrous carbon in the composite is not unevenly distributed and is uniformly adsorbed on the active material. By satisfying these two conditions, the fibrous carbon in the composite is crushed and is thin and uniformly adsorbed on the active material, and when it is used as an electrode for a secondary battery, it reduces the electrode resistance and favors the formation of an electronic conduction path to the active material during the battery reaction, improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, making it possible to improve the battery capacity.
[0025] <Negative electrode active material> The negative electrode active material is not particularly limited. For example, it can be metallic Li capable of reversibly doping or intercalating lithium ions, or its alloy, tin alloy, silicon-based material (such as metallic Si, Si alloy, SiO x etc.), Li X TiO2, Li X Fe2O3, Li X Fe3O4, Li X metal oxide-based materials such as WO2, conductive polymers such as polyacetylene and poly-p-phenylene, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can be used alone or in combination of two or more. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials, etc.
[0026] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, having a high aspect ratio in the long axis direction, and it is easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). CNT has a shape in which planar graphite is wound into a cylindrical shape, including single-layer CNT, bilayer CNT, thin-layer (several layers) CNT, and multi-layer CNT, and these may be mixed. Single-layer CNT has a structure in which one layer of graphite is wound. Multi-layer CNT has a structure in which two or more layers of graphite are wound. Also, the side wall of CNT does not have to be a graphite structure. Also, for example, CNT having a side wall with an amorphous structure is also CNT in this specification.
[0027] The shape of the CNT is not limited. Examples of such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stack type), trump-like (platelet) and coil-like. Among them, the shape of the CNT is preferably needle-like or cylindrical tube-like. The CNT may be a single shape or a combination of two or more shapes.
[0028] Examples of the form of CNT include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.
[0029] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it becomes difficult to adjust the volume resistivity to 1000 Ω·cm or less. In addition, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. In addition, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.
[0030] The content of fibrous carbon in the composite is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, based on the mass of the composite for secondary battery electrodes. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.
[0031] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.
[0032] <Binder resin> The composite of the present invention may contain a binder resin as necessary. The binder resin is not particularly limited as long as it is normally used as a binder resin, and can be appropriately selected according to the purpose. The binder resin used in the composite is preferably a resin capable of binding between substances such as active materials and fibrous carbon. Examples of the binder resin used in the composite include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose-based resins such as carboxymethylcellulose; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Among these, carboxymethylcellulose, styrene-butadiene rubber, and polyacrylic acid are preferred.
[0033] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.
[0034] <Method of manufacturing a composite for secondary battery electrode> The method for compounding the negative electrode active material with the fibrous carbon or the like is not particularly limited. For example, there may be mentioned a method of mixing the active material and fibrous carbon in a dry state, a method of mixing by adding a solvent, or a method of preparing a slurry and mixing in a wet state. In order to prepare a more uniform composite, a method of mixing using a dispersion liquid in which fibrous carbon or the like is dispersed in a solvent in advance is preferred. Among them, the use of a fibrous carbon dispersion is preferred because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Even if a fibrous carbon dispersion is not used, it is preferred because the same effect can be obtained by breaking up the agglomerates of the fibrous carbon using a high shear force composite machine or the like. The combination of a fibrous carbon dispersion and a high shear force composite machine is particularly preferred.
[0035] Examples of dry mixers include: Examples of such equipment include roll mills with two or three rolls, high-speed agitators such as Henschel Mixers and Super Mixers, fluid energy grinders such as Micronizers and Jet Mills, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro," mixers manufactured by Inoue Manufacturing Co., Ltd. such as "Planetary Mixer" and "Trimix," and mixer / granulator "High Speed Mixer" manufactured by EarthTechnica.
[0036] In addition, when using a dry mixer, other raw materials such as fibrous carbon may be added directly in powder form to the active material as the base material, but in order to create a more uniform mixture, it is preferable to disperse or dissolve the other raw materials such as fibrous carbon in a small amount of solvent in advance and then mix them. Among these, the use of a fibrous carbon dispersion is preferable because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Furthermore, in order to increase the processing efficiency, it may be preferable to heat the mixture. Among dry mixers, a planetary mixer, trimix, or mechanofusion, which is capable of compounding by shearing, is preferable.
[0037] Examples of wet mixing devices include: Mixers such as dispersers, homomixers, or planetary mixers; Mixers such as M Technique's "Clearmix" or PRIMIX's "Fillmix"; Rotation and revolution type mixers such as THINKY's "Awatori Rentaro" Media-type dispersing machines such as a paint conditioner (manufactured by Red Devil), a ball mill, a sand mill (such as "Dyno Mill" manufactured by Shinmaru Enterprises), an attritor, a pearl mill (such as "DCP Mill" manufactured by Eirich), or a Coball mill; Wet jet mills (such as Genus PY, Sugino Machine Starburst, and Nanomizer), M-Technique Claire SS-5, and Nara Machinery Micros media-less dispersers; Spray dryers such as Okawara Chemical Engineering Spray Dryers Other examples include, but are not limited to, roll mills, kneaders, etc. In addition, it is preferable to use a wet mixing device that has been treated to prevent metal from entering the device. When a media-type dispersing machine such as a ball mill is used, there is a risk that the structure of the active material may be destroyed by mixing, so a media-less dispersing machine is preferred.
[0038] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a dispersion medium, and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.
[0039] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 μm or more, and is preferably 5.0 μm or less, and more preferably 2.0 μm or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, making it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.
[0040] The viscosity of the fibrous carbon dispersion, measured using a B-type viscometer at 25°C and 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.
[0041] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 6 rpm measured at 25°C with a B-type viscometer by the viscosity (mPa·s) at 60 rpm. The TI value is preferably 1.0 or more and less than 10.0, more preferably 1.0 or more and less than 5.0, and even more preferably 1.0 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, dispersant, and other resin components, or the intermolecular forces thereof, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, the entanglement of the fibrous carbon, dispersant, and other resin components can be suppressed while allowing these intermolecular forces to act appropriately.
[0042] The average fiber length of the fibrous carbon in the fibrous carbon dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon in the fibrous carbon dispersion can be calculated by diluting the fibrous carbon dispersion 50 times with a solvent, dropping the diluted fibrous carbon dispersion onto a substrate, drying the substrate, observing the sample with a scanning electron microscope, and randomly selecting 300 pieces of fibrous carbon from the observation photograph and measuring the fiber length of each piece.
[0043] The content of the fibrous carbon is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 0.8% by mass or more, based on the total amount of the fibrous carbon dispersion. Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting it within the above range, the fibrous carbon can be present well and stably without causing sedimentation or gelation. It is more preferably 0.1 to 20% by mass, and even more preferably 0.5 to 10% by mass. Also, it is preferable that the content of the fibrous carbon is appropriately adjusted so that a fibrous carbon dispersion liquid with appropriate fluidity or viscosity is obtained depending on the specific surface area of the fibrous carbon, affinity to the dispersion medium, dispersibility of the dispersant, etc.
[0044] The content of the dispersant is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 15 to 80 parts by mass, relative to 100 parts by mass of the fibrous carbon. The content of the dispersant is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass, relative to the total amount of the fibrous carbon dispersion.
[0045] The solid content of the fibrous carbon dispersion is preferably from 0.2 to 40 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %.
[0046] The fibrous carbon dispersion may be prepared by separately preparing two or more kinds of fibrous carbon having different average outer diameters and adding them to a dispersion medium. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the average outer diameter of the first fibrous carbon is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second fibrous carbon is preferably 5 nm or more and 30 nm or less, more preferably 20 nm or less. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the mass ratio of the first fibrous carbon to the second fibrous carbon is preferably 1:10 to 1:100, more preferably 1:10 to 1:50.
[0047] The average fiber length of the fibrous carbon is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a scanning electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the fiber length of each piece.
[0048] The aspect ratio is the fiber length of the fibrous carbon divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. A conductive material with a higher aspect ratio can provide higher conductivity when formed into an electrode. The aspect ratio of the fibrous carbon is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.
[0049] The specific surface area of fibrous carbon is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and2 / g or less is more preferable. The specific surface area of the fibrous carbon is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area of the fibrous carbon are within the above ranges, a conductive path developed in the electrode is easily formed.
[0050] The carbon purity of the fibrous carbon is represented by the content (mass%) of carbon atoms in the fibrous carbon, and is preferably 80 mass% or more relative to 100 mass% of the fibrous carbon.
[0051] For the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity, fibrous carbon that has been subjected to a purification treatment may be used.
[0052] When fibrous carbon is dispersed in a disperser by collision with media such as a bead mill, or when it is repeatedly passed through a disperser over a long period of time, the fibrous carbon may be broken and short-flaked carbonaceous matter may be generated. When short-flaked carbonaceous matter is generated, the viscosity of the fibrous carbon dispersion decreases, and the gloss of the coating film obtained by coating and drying the fibrous carbon dispersion increases. Judging from these evaluation results alone, however, the short-flaked carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may worsen the resistance of the electrode. The degree of short-flaked carbonaceous matter generation can be confirmed by diluting the dispersion liquid, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, and drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion liquid so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.
[0053] The fibrous carbon may be produced by any method. The fibrous carbon can generally be produced by, but is not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method. For example, the fibrous carbon can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. The carbon source may be at least one of a hydrocarbon and an alcohol.
[0054] <Dispersant> The dispersant for the fibrous carbon dispersion is preferably one that can disperse and stabilize the fibrous carbon in the fibrous carbon dispersion. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption power to the fibrous carbon and can provide good dispersion stability. Depending on the characteristics required for dispersing the fibrous carbon, a suitable type of dispersant can be used in a suitable amount.
[0055] Examples of the resin-type dispersant that can be used include (meth)acrylic polymers, polymers derived from ethylenically unsaturated hydrocarbons, cellulose derivatives, and copolymers thereof. Examples of the polymers derived from ethylenically unsaturated hydrocarbons include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, and nitrile rubbers. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, and amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, and polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with acetal (acetoacetal-modified or butyral-modified, etc.) by aldehydes. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, JP 2019-087304 A, Japanese Patent No. 6524479 A, and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are cellulose derivatives, polyvinyl alcohol, polyvinyl butyral, polyvinylpyrrolidone, and polyacrylonitrile polymers. Polymers in which other substituents have been introduced into a portion of these polymers, modified polymers, and the like may also be used. The weight-average molecular weight of the resin-type dispersant is preferably 5,000 to 300,000, more preferably 10,000 to 100,000, and even more preferably 10,000 to 50,000, in terms of pullulan, from the viewpoint of the affinity balance between the dispersed substance and the dispersion medium and the viewpoint of resistance to the electrolyte. The resin-type dispersant may be used alone or in combination of two or more kinds.
[0056] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, and Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Commercially available polyvinylpyrrolidone resins include, specifically, polyvinylpyrrolidone K30, K90 (manufactured by Fujifilm Wako), and K120 (manufactured by DSP Gokei Food & Chemical). Commercially available nitrile rubbers are available in various grades with different nitrile ratios, hydrogenation rates, and molecular weights under trade names such as Therban (hydrogenated nitrile rubber manufactured by Aranseo), Baymod (nitrile rubber manufactured by Aranseo), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and NipoleNBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by known synthesis methods may be used. Surfactants may be used in place of or in addition to the above-mentioned resin-type dispersants. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.
[0057] As the resin-type dispersant, a polymer containing at least an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit may be used. The aliphatic hydrocarbon structural unit of the polymer may contain an alkylene structural unit. The polymer may be hydrogenated.
[0058] The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.
[0059] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, and an alkanetetrayl structural unit. Structural units containing a branch point, such as an alkanetriyl structural unit and an alkanetetrayl structural unit, are structural units different from structural units containing a branched alkylene structure and structural units containing a branched alkyl structure, which will be described later. The aliphatic hydrocarbon structural unit preferably contains at least an alkylene structural unit.
[0060] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.
[0061] It is preferable to add a base to the resin composition, since it enhances the wettability of the fibrous carbon in the dispersion medium, improves the dispersibility, and improves the dispersion stability. The base to be added may be at least one selected from the group consisting of inorganic bases, inorganic metal salts, organic bases, and organic metal salts.
[0062] Examples of inorganic bases and inorganic metal salts include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, borates, and ammonium hydroxides of alkali metals or alkaline earth metals. Among these, hydroxides or alkoxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal contained in the inorganic base may be a transition metal.
[0063] Examples of the organic base include primary, secondary and tertiary amine compounds having 1 to 40 carbon atoms (eg, alkylamines and amino alcohols) which may have a substituent, and organic hydroxides.
[0064] Examples of organic metal salts include alkoxides of alkali metals and acetates of alkali metals. Examples of alkoxides of alkali metals include lithium methoxide, lithium ethoxide, lithium propoxide, lithium t-butoxide, lithium n-butoxide, sodium methoxide, sodium ethoxide, sodium propoxide, sodium t-butoxide, sodium n-butoxide, potassium methoxide, potassium ethoxide, potassium propoxide, potassium t-butoxide, and potassium n-butoxide. Among these, sodium t-butoxide is preferred from the viewpoint of easily supplying cations. The metal of the inorganic base may be a transition metal.
[0065] The amount of the base used is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, based on the mass of the polymer. The amount of the base used is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the mass of the polymer. If the amount used is too small, the decrease in Mooney viscosity tends not to occur easily. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0066] In addition to the above-mentioned dispersant, the fibrous carbon dispersion may further contain an inorganic base, an inorganic metal salt, an organic base, an organic metal salt, or a combination thereof. The total amount of these is preferably 0.001 to 0.1 mass%, more preferably 0.005 to 0.05 mass%, based on the total amount of the resin composition.
[0067] <Dispersion medium> The solvent is not particularly limited as long as it can disperse carbon nanotubes, but is preferably water and / or a mixed solvent consisting of one or more water-soluble organic solvents, and more preferably contains water. When water is contained, the amount of water is preferably 95 parts by mass or more, and more preferably 98 parts by mass or more, based on the total amount of the solvent.
[0068] Examples of the water-soluble organic solvent include alcohols (methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, benzyl alcohol, etc.), polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol, hexanediol, pentanediol, glycerin, hexanetriol, thiodiglycol, etc.), polyhydric alcohol ethers (ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, etc.), and amines ( Ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenediamine, triethylenetetramine, tetraethylenepentamine, polyethyleneimine, pentamethyldiethylenetriamine, tetramethylpropylenediamine, etc.), amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), as well as tetrahydrofuran, urea, acetonitrile, etc. can be used.
[0069] Examples of the method for removing the liquid medium and drying include hot air drying, vacuum drying, spray drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.
[0070] <Slurry for secondary battery electrode composite material> A slurry for a secondary battery electrode can be prepared using the composite for a secondary battery electrode. A composite slurry for a secondary battery electrode can be obtained by adding the composite for an electrode and a binder resin to a dispersion medium. If necessary, a fibrous carbon dispersion and other optional components may be appropriately contained within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination thereof. The optional components may be those described above for the fibrous carbon dispersion. The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material".
[0071] The solid content in the composite slurry is preferably 20% by mass or more, more preferably 30% by mass or more, based on the mass of the composite slurry (mass of the composite slurry being 100% by mass), and is preferably 90% by mass or less, more preferably 80% by mass or less.
[0072] The content of the electrode composite in the composite slurry is preferably 28% by mass or more, more preferably 38% by mass or more, and even more preferably 48% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 88% by mass or less, and more preferably 80% by mass or less.
[0073] The content of the binder resin in the composite slurry is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less. When the electrode composite contains a binder resin, it is preferable to adjust the total amount of the binder resin in the composite slurry to be within the above range.
[0074] The content of fibrous carbon in the composite slurry is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less. Since the electrode composite of the present invention contains fibrous carbon, it is preferable to adjust the total amount of fibrous carbon in the composite slurry to be within the above range. If it exceeds the above range, the filling amount of the active material in the electrode decreases, resulting in a low capacity of the battery. Also, if it is below the above range, the conductivity of the electrode and the battery may be insufficient.
[0075] <Method for producing secondary battery electrode composite slurry> In the method for preparing the composite slurry, the order of adding the electrode composite and the binder resin to the dispersion medium is not particularly limited. For example, a method of preparing the binder resin by adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition; a method of preparing the electrode composite by adding the binder resin to the dispersion medium and then adding the binder resin; a method of preparing the binder resin and the electrode composite by adding them all at once to the dispersion medium, and the like can be mentioned. As a method for preparing the composite slurry, a method of adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition and performing a stirring process is preferable. The stirring device used for stirring is not particularly limited. A disperser, a homogenizer, etc. can be used as the stirring device.
[0076] <Electrode for secondary batteries> The secondary battery electrode in the present invention includes a composite for secondary battery electrodes. The electrode may further include an optional component such as a dispersant. The electrode can be formed by preparing the above-mentioned composite slurry and applying the composite slurry, or by mixing each component of the composite for secondary battery electrodes in a dry state without using the composite slurry, and forming it into a sheet by pressing or the like. When the composite slurry is used, for example, the electrode film can be formed by applying the composite slurry to a current collector and removing volatiles.
[0077] <Method of manufacturing secondary battery electrodes> The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.
[0078] The method of applying the composite slurry onto the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after application, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.
[0079] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode and pressing each component into a sheet without using a composite slurry, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure-molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed on the current collector in advance.
[0080] Examples of the method for pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.
[0081] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and includes an electrode film made from the composite of the present invention.
[0082] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector. The negative electrode may be an electrode film containing a negative electrode active material formed on a current collector. The negative electrode active material may be any of the above-mentioned materials.
[0083] The positive electrode active material is not particularly limited, but may be a metal compound such as a metal oxide or metal sulfide capable of doping or intercalating lithium ions, or a conductive polymer. Examples of the material include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium, and inorganic compounds such as transition metal sulfides. Specifically, MnO, VO, VO 13 Examples of the conductive material include transition metal oxide powders such as TiO2, composite oxide powders of lithium and transition metals such as lithium nickel oxide, lithium cobalt oxide, lithium manganate, and lithium manganate having a spinel structure, lithium iron phosphate-based materials that are phosphate compounds having an olivine structure, and transition metal sulfide powders such as TiS2 and FeS. Conductive polymers such as polyaniline, polyacetylene, polypyrrole, and polythiophene can also be used. The above inorganic compounds and organic compounds may also be used in combination.
[0084] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.
[0085] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0086] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.
[0087] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.
[0088] In the composite for secondary battery electrodes of the present invention, the active material and the fibrous carbon are uniformly composited in advance, and therefore the composite can be suitably used not only for electrodes prepared from the composite slurries exemplified above, but also for electrodes prepared by solid or semi-solid processes, and can be applied not only to lithium ion secondary batteries using conventional electrolyte solutions, but also to all-solid batteries, semi-solid batteries, and the like.
[0089] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES
[0090] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0091] <Dispersant> CMC: Sunrose APP-84: Carboxymethylcellulose (manufactured by Nippon Paper Industries Co., Ltd.) PAA: Julimer AC-10LP (manufactured by Toagosei)
[0092] (Production Example 1: Production of PAN) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of acetonitrile and substituted with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture of 75.0 parts of acrylonitrile, 25.0 parts of acrylic acid, and 5.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (NOF Corp.; V-65) was added dropwise over 3 hours to carry out a polymerization reaction. After completion of the dropwise addition, the reaction was continued for another hour at 70°C, and then 0.5 parts of V-65 was added and the reaction was continued for another hour at 70°C. Thereafter, the conversion rate was confirmed to exceed 98% by measuring the non-volatile content, and the dispersion medium was completely removed by vacuum concentration to obtain a dispersant. The weight average molecular weight (Mw) of the dispersant was 15,000.
[0093] In the examples and comparative examples, the following fibrous carbon was used. ·10B: JENOTUBE10B (manufactured by JEIO, multilayer CNT, average outer diameter 10 nm, specific surface area 230 m 2 / g) ·6A:JENOTUBE6A (manufactured by JEIO, multilayer CNT, average outer diameter 6nm, specific surface area 700m 2 / g) TUBALL (OCSiAl, single-walled CNT, average outer diameter 1.6 nm, carbon purity 93%, specific surface area 975 m 2 / g)
[0094] In the examples and comparative examples, the following active materials were used. Natural graphite (Nippon Graphite Industries Co., Ltd., CGB-20) SiO (without carbon coating): Silicon monoxide (manufactured by Osaka Titanium Technology Co., Ltd., SILICONMONOOXIDE) SiO (with carbon coating): Silicon monoxide (manufactured by Osaka Titanium Technology Co., Ltd., SILICONMONOOXIDE) Hereafter, SiO (with carbon coating) will be abbreviated as SiO.
[0095] <Preparation of fibrous carbon dispersion> (Production Example 1) According to the materials and compositions shown in Table 1, a fibrous carbon dispersion was prepared as follows. First, ion-exchanged water was placed in a stainless steel container and heated to 50°C. After adding the dispersant and additives while stirring with a disperser, the mixture was stirred for 1 hour to dissolve the dispersant. Next, the fibrous carbon was added while stirring with a disperser, and a square-hole high-shear screen was attached to a high-shear mixer (L5M-A, manufactured by SILVERSON). The mixture was dispersed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. At this time, the dispersion particle size confirmed by the grind gauge was 220 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The dispersion liquid was dispersed until the viscosity at 60 rpm measured with a B-type viscometer (TOKISANGYO, VISCOMETER, MODEL: BL) was 3,000 mPa s or less. After that, a pass-type dispersion process was performed using a high-pressure homogenizer according to the number of passes shown in Table 1, and fibrous carbon dispersion 1 was obtained.
[0096] (Production Examples 2 to 5) Fibrous carbon dispersions 2 to 5 were obtained in the same manner as in Production Example 1, except that the materials, compositions, and number of passes were changed according to those shown in Table 1.
[0097] [Table 1] The additives listed in Table 1 are as follows. ·NaCO3: Anhydrous sodium carbonate (Kishida Chemical Co., Ltd.)
[0098] <Electrode composite for secondary batteries> (Example 1-1) A composite for secondary battery electrodes was prepared using a high-speed mixer made by EarthTechnica Corporation according to the composition shown in Table 2. SiO and fibrous carbon dispersion 1 were stirred at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm, and then dried in an oven at 100°C for 2 hours to obtain composite 1.
[0099] (Example 1-2) According to the composition shown in Table 2, fibrous carbon dispersion 1 and water were weighed out and placed in a stainless steel container, and SiO was added while stirring with a disperser, and then the mixture was stirred for 60 minutes to obtain a slurry. The slurry was spray-dried at 150°C using a spray dryer, Mini Spray Dryer B-290, manufactured by Nippon Buchi Co., Ltd., to obtain Composite 2.
[0100] (Examples 1-3 to 1-7) According to the compositions shown in Table 2, Composites 3 to 7 were obtained in the same manner as in Example 1-2.
[0101] (Examples 1 to 8) A composite for secondary battery electrodes was produced using a high-shear composite machine Mechanofusion manufactured by Hosokawa Micron Corporation according to the composition shown in Table 2. Composite 8 was obtained by stirring the mixture of SiO and Dispersion 1 at a rotation speed of 3500 rpm for 10 minutes.
[0102] (Examples 1-9, 11, 12, and 14) Composites 9, 11, 12, and 14 were obtained in the same manner as in Examples 1-8 according to the compositions shown in Table 2.
[0103] (Examples 1-10, 13, and 15) Composites 10, 13, and 15 were obtained in the same manner as in Examples 1-8, except that the rotation speed of the high-shear multifunction machine Mechanofusion manufactured by Hosokawa Micron Corporation was changed to 6,000 rpm according to the composition shown in Table 2.
[0104] (Examples 1 to 16) A composite for a secondary battery electrode was prepared using a planetary mixer manufactured by PRIMIX Corp., according to the composition shown in Table 2. A mixture of SiO (without carbon coating) and fibrous carbon dispersion 1 was stirred at a rotation speed of 30 rpm for 70 minutes, and then dried in an oven at 100°C for 2 hours to obtain composite 16.
[0105] (Examples 1-17) A composite for a secondary battery electrode was prepared using a planetary mixer manufactured by PRIMIX Corp., according to the composition shown in Table 2. The mixture of SiO and fibrous carbon dispersion 1 was stirred at a rotation speed of 30 rpm for 70 minutes, and then dried in an oven at 100°C for 2 hours to obtain composite 17.
[0106] (Examples 1-18, 19, 20, 21, and 23) Composites 18, 19, 20, 21, and 23 were obtained in the same manner as in Examples 1-17, except that the rotation speed of the planetary mixer was changed to 50 rpm and stirring was performed for 40 minutes according to the compositions shown in Table 2.
[0107] (Examples 1-22 and 24) Composites 22 and 24 were obtained in the same manner as in Examples 1-17, except that the rotation speed of the planetary mixer was changed to 75 rpm and stirring was performed for 30 minutes according to the composition shown in Table 2.
[0108] (Comparative Examples 1-1, 2, 3) According to the compositions shown in Table 2, SiO and fibrous carbon (10B, 6A, TUBALL) were weighed into a container and stirred with a medicine spoon for 10 minutes to obtain composites 25, 26, and 27.
[0109] (Comparative Examples 1-4) A composite for secondary battery electrodes was prepared using a high-speed mixer made by EarthTechnica Corporation according to the composition shown in Table 2. Composite 28 was obtained by mixing SiO and 10B at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm.
[0110] (Comparative Examples 1-5) According to the composition shown in Table 2, SiO (without carbon coating) and fibrous carbon (10B) were weighed out into a container and stirred with a medicine spoon for 10 minutes to obtain Composite 29.
[0111] The temperature of the exothermic peak and the volume resistivity were measured by the method described herein.
[0112] [Table 2] *1: SiO (without carbon coating) was used.
[0113] <Preparation of negative electrode mixture slurry and negative electrode> (Example 2-1) In a plastic container, 25.0 parts by mass of an aqueous solution in which 2% by mass of sodium carboxymethylcellulose was dissolved, and 17.3 parts by mass of ion-exchanged water were weighed. Then, using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310), the mixture was stirred at 2000 rpm for 1 minute to obtain a carbon resin composition. Then, 5.0 parts by mass of composite 1 was added, and the mixture was stirred at 2000 rpm for 5 minutes using the centrifugal mixer. Furthermore, 43.7 parts by mass of natural graphite (Nippon Graphite Industries Co., Ltd., CGB-20) was added, and the mixture was stirred at 2000 rpm for 5 minutes using the centrifugal mixer. Then, 1.6 parts by mass of styrene butadiene emulsion was added, and the mixture was stirred at 2000 rpm for 30 seconds using the centrifugal mixer to obtain a negative electrode composite material slurry 1.
[0114] (Examples 2-2, 5, 6, 8, 16, 17, Comparative Examples 2-1 to 2-5) Except for changing the compositions and amounts added to those shown in Table 3, composite slurries 2, 5, 6, 8, 16, 17, and 25 to 29 were obtained in the same manner as composite slurry 1.
[0115] (Example 2-3) In a plastic container, 1.7 parts by mass of dispersion 2, 25.0 parts by mass of an aqueous solution in which 2% by mass of sodium carboxymethylcellulose was dissolved, and 15.4 parts by mass of ion-exchanged water were weighed. Then, using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310), the mixture was stirred at 2000 rpm for 1 minute to obtain a carbon resin composition. Then, 4.9 parts by mass of composite 3, which is a negative electrode active material, was added, and the mixture was stirred at 2000 rpm for 5 minutes using the centrifugal mixer. Furthermore, 43.7 parts by mass of natural graphite (Nippon Graphite Industries Co., Ltd., CGB-20) was added, and the mixture was stirred at 2000 rpm for 5 minutes using the centrifugal mixer. Then, 1.6 parts by mass of styrene butadiene emulsion was added, and the mixture was stirred at 2000 rpm for 30 seconds using the centrifugal mixer to obtain a negative electrode composite material slurry 3.
[0116] (Examples 2-4, 9-15, 18-24) Except for changing the composition and the amounts added as shown in Table 3, the same procedure as for composite slurry 3 was carried out to obtain composite slurry 4, 9 to 15, and 18 to 24.
[0117] (Examples 2-7) In a plastic container, 1.2 parts by mass of Dispersion 1, 25.0 parts by mass of an aqueous solution in which 2% by mass of sodium carboxymethylcellulose was dissolved, and 17.3 parts by mass of ion-exchanged water were weighed. Then, using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310), the mixture was stirred at 2000 rpm for 1 minute to obtain a carbon resin composition. Then, 4.9 parts by mass of silicon monoxide (with carbon coating) (Osaka Titanium Technology Co., Ltd., SILICONMONOOXIDE, SiO 1.3C 5μm) which is a negative electrode active material was added, and the mixture was stirred at 2000 rpm for 5 minutes using the centrifugal mixer. Furthermore, 43.8 parts by mass of Composite 7 was added, and the mixture was stirred at 2000 rpm for 5 minutes using the centrifugal mixer. Thereafter, 1.6 parts by mass of styrene-butadiene emulsion was added, and the mixture was stirred at 2000 rpm for 30 seconds using the centrifugal mixer to obtain negative electrode mixture slurry 7.
[0118] In Examples 2-1 to 2-24, the total amount of CNT contained in each electrode is as follows. When using 10B or 6A: 0.3% When using TUBALL: 0.08%
[0119] The negative electrode composite slurry was applied to the electrode using an applicator so that the weight per unit area of the electrode was 8 mg / cm. 2 After coating on copper foil so that the density of the composite layer became 1.6 g / cm, the coating film was dried in an electric oven at 120°C ± 5°C for 30 minutes. Next, the coating film was rolled using a roll press (Thank Metal Co., Ltd., 3 ton hydraulic roll press) to reduce the density of the composite layer to 1.6 g / cm. 3 Thus, an electrode film having the following structure was obtained.
[0120] <Assembly of a cell for evaluating the negative electrode of a lithium-ion secondary battery> Negative electrodes 1 to 29 were punched out to φ16 mm to be used as working electrodes, metallic lithium foil (thickness 0.15 mm) to be used as counter electrodes, a separator (porous polypropylene film) was inserted between the working electrode and the counter electrode, and the electrolyte (a non-aqueous electrolyte in which LiPF6 was dissolved at a concentration of 1M in a mixed solvent in which ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1) was filled to assemble a bipolar sealed metal cell (Hosen HS Flat Cell). The cell was assembled in a glove box substituted with argon gas.
[0121] <Evaluation of cycle characteristics of negative electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery negative electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C with a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the negative electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed by the ratio of the 3rd 0.2C discharge capacity to the 200th 0.2C discharge capacity, as shown in the following formula 1. (Formula 1) Cycle characteristic = 3rd 0.2C discharge capacity / 200th 0.2C discharge capacity × 100 (%) The relative value (%) was calculated based on the cycle characteristic of Comparative Example 2-4, and the results were evaluated according to the following criteria. Cycle performance criteria ◎: 180% or more (excellent) ○: 150% or more but less than 180% (Excellent) ○△: 120% or more but less than 150% (good) △: 100% or more but less than 120% (defective) ×: Less than 100% (extremely poor)
[0122] [Table 3]
[0123] As shown in Table 3, the Examples showed superior battery characteristics compared to the Comparative Examples. Among them, in Examples 2-3, 5, 6, 10, 12 to 15, 18, and 21 to 24, in which the volume resistivity and heat generation peak temperature of the composite were in the most suitable ranges, it was confirmed that the obtained electrodes had excellent battery characteristics due to the low resistance. In the comparative examples, the volume resistivity and exothermic peak temperature of the composite were outside the appropriate ranges, and it is believed that the fibrous carbon aggregated and did not form a uniform composite state, leading to deterioration of the electrode resistance and battery characteristics. From the above, it was demonstrated that an electrode composite within the parameter range of the present invention can exhibit excellent battery characteristics regardless of the manufacturing method.
Claims
1. A composite for a secondary battery electrode comprising fibrous carbon and a negative electrode active material, characterized in that the fibrous carbon has an exothermic peak temperature of 530°C or less as determined by simultaneous thermogravimetry and differential thermal analysis under an oxygen atmosphere, and has a volume resistivity of 1000 Ω cm or less under a load of 20 kN.
2. 2. The composite for a secondary battery electrode according to claim 1, wherein the content of the fibrous carbon is 20 mass % or less based on the mass of the composite for a secondary battery electrode.
3. 3. A secondary battery electrode comprising the composite for a secondary battery electrode according to claim 1 or 2.
4. A secondary battery comprising the electrode for a secondary battery according to claim 3 .
5. A vehicle or device comprising the secondary battery according to claim 4.
Citation Information
Patent Citations
Granular composite carbon material and its manufacturing method, and negative electrode material for lithium ion secondary cell, negative electrode for lithium ion secondary cell and lithium ion secondary cell
JP2006008462A